Evaluation of the effect of fodder tree leaflitter and earthworms on sorghum growth in the greenhouse. - Ávila, Marco; Bautista, Francisco; Huerta, Esperanza; Meléndez, Virginia (Instituto de Ecología, A.C., 2010)
Under greenhouse conditions we analyzed the effect of litter quality of the arboreal species Diospyros cuneata, Bursera simaruba, Caesalpinia gaumeri, Randia longiloba, Gymnopodium floribundum and Piscidia piscicula, and inoculation of the earthworm Dichogaster bolaui, on sorghum growth. Plastic pots were used containing 2 kg of soil, 100 g of foliage of each plant and 1.2 g of earthworms. The experimental design was completely randomized and the data submitted to ANOVA and principal components analysis to study the relationships between litter quality, sorghum growth and earthworm biomass. The foliage of B. simaruba and G. floribundum that have higher phosphorus favored the higher sorghum biomass, with or without earthworms, although plant heights were correlated with higher ratios of Detergent Fibre/N. Earthworm inoculation increased total biomass and the height of the sorghum plants. The foliage of R. longiloba and C. gaumeri favors the populations of D. bolaui but not sorghum plant growth. In the group of treatments with earthworms, the foliage of P. piscipula and D. cuneata supported favorable populations of earthworms, but did not benefit sorghum growth.